O45 Participants' perception of in situ simulation related anxiety: a multi-disciplinary study. (5th November 2017) - Collins, Sami; Korb, C; Lofton, L; Raimalwalla, T; Sampaio, H; West, N; Lane, M; Burmester, M
Abstract : Background: Simulation related anxiety is prevalent amongst all healthcare professions. In excess, this stress can impact learning and performance through cognitive overload. 1 The Simulated Inter-Professional Team Training (SPRinT) programme runs regular 2-hourly high-fidelity in situ simulation courses to frontline interprofessional teams focusing on crisis resource management. Scenarios derive from real events and utilise real medications and equipment. Raising awareness of participant anxiety may help simulation faculty to adapt their approach, ensuring participants' anxiety is recognised and managed to support learning. We aim to identify state and trait anxiety levels perceived by participants of SPRinT courses and the influence of repeat attendance on anxiety. Methodology: Prospective pre and post-course anonymous survey of SPRinT course participants from May until October 2017 using the adapted short-form State Trait Anxiety Inventory (STAI). 2 STAI utilises level of agreement with anxiety present and anxiety absent descriptors to identify both state and trait anxiety levels consciously perceived by individuals. Participants will consider the same statements immediately before and after participating in SPRinT courses. Anxiety scores will then be calculated with comparison between pre and post-course scores as well as according to number of previous SPRinT courses attended by participants. Qualitative data will be collected by additional open questions after participating in a SPRinT course. Anticipated Results: A retrospective review of evaluation data from SPRinT courses between January 2014-April 2017 (593 participants' feedback over 79 courses) demonstrated that participants reported high levels of agreement related to questions about realism of scenario environment and stress level [median 82% (IQR 70%–90%) and 80% (IQR 65%–90%) respectively]. We anticipate that the results of this research will highlight that anxiety is widely felt by participants. We also expect that, first time SPRinT course participants may feel initial heightened levels of anxiety in the lead up to a SPRinT course which will reduce following participation. Anticipated Conclusion: Participants of SPRinT courses perceive high levels of state and trait anxiety immediately before the session, which is heightened for first time participants. Both state and trait anxiety levels reduce after attending the course. Psychological safety is vital in maintaining an environment conductive for learning. Some level of anxiety is to be expected prior to simulation; improved understanding of anxiety levels and how it is felt should allow faculty to support participants to overcome this. Identifying ways to reduce the initial anxiety will contribute toward adapting the SPRinT course delivery to optimise the learning. References: . Bong CL, Fraser K, Oriot D. Cognitive load and stress in simulation. In VJ Grant, A Cheng (Eds.), Comprehensive healthcare simulation: Paediatrics 2016:3–18. Switzerland: Springer. . Tluczec A, Henriques JB, Brown RL. Support for the reliability and validity of a six-item state anxiety scale derived from the state trait anxiety inventory. Journal of Nursing Measurement 2009;17(1):19–28.